Severe plastic deformation as a processing tool for strengthening of additive manufactured alloys. (August 2021) - Hosseinzadeh, Ali; Radi, Amin; Richter, Julia; Wegener, Thomas; Sajadifar, Seyed Vahid; Niendorf, Thomas; Yapici, Guney Guven
Abstract: For the first time, the novel combination of multi-pass equal channel angular extrusion/pressing (ECAE/P) and selective laser melting (SLM) was investigated. Herein, four passes of ECAP via route Bc at 150 °C were applied as a severe plastic deformation (SPD) technique on the SLM as-built AlSi12 to promote superior mechanical properties. The microstructure and mechanical behavior of AlSi12 fabricated by SLM were studied before and after ECAP, applying several mechanical and microstructural characterization techniques. Results of the tensile experiments revealed that the yield point, the ultimate strength, and the ductility of the as-built sample were improved by 56%, 11%, and 55% after 4 passes of ECAP, respectively. This enhancement is attributed to the effective grain refinement and the persisting silicon phase network after SPD as evidenced by electron backscatter diffraction and elemental mapping results. Moreover, micro-computed tomography analysis disclosed that ECAP considerably reduces the remnant porosity of the post-treated SLM AlSi12 samples eventually further affecting the strength of the ultra-fine grained AlSi12 in a positive way. Findings presented herein indicate that it is viable to utilize ECAP as a post-AM processing tool for mechanical property improvement of laser powder bed fused microstructures with the virtue of enhanced densification. Even if geometrical restrictions exist in ECAP, results obtained herein are transferrable to other SPD techniques with suitable processing windows, which would pave the way to advanced properties of adequately post-treated conditions.